2014
DOI: 10.1111/dsji.12020
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation into the Adaptive Learning Styles of Business Students

Abstract: An exploration of the preferred learning styles for over 1,100 business students has yielded an intriguing result. While many previous studies have examined the learning styles in different majors at different universities, these studies have been focused on describing the typical student for that major. This study demonstrates that the preferred learning styles of students may depend more on the course than the major, indicating that students may have adaptive learning styles. Rather than having an innate, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…In pursuit of an answer to this question, Kellogg and Smith () studied the “blending” of online and student‐to‐student interactions, finding that in many cases the effects of in‐person student‐to‐student interactions can actually be negative. This result may be viewed in conjunction with the findings of Sandman () that suggested that students have adaptive learning styles which can change based on the subject of the course. Scholars have also examined how changing demographics and behavioral patterns of newer generations of students impact the way in which they learn, finding that millennial generation students require the instructor to motivate them more so than in previous generations (Nargundkar & Shrikhande, ).…”
Section: Online Education Assessment and CIsupporting
confidence: 71%
“…In pursuit of an answer to this question, Kellogg and Smith () studied the “blending” of online and student‐to‐student interactions, finding that in many cases the effects of in‐person student‐to‐student interactions can actually be negative. This result may be viewed in conjunction with the findings of Sandman () that suggested that students have adaptive learning styles which can change based on the subject of the course. Scholars have also examined how changing demographics and behavioral patterns of newer generations of students impact the way in which they learn, finding that millennial generation students require the instructor to motivate them more so than in previous generations (Nargundkar & Shrikhande, ).…”
Section: Online Education Assessment and CIsupporting
confidence: 71%
“…The impetus behind this study was to suggest that applying the principles of CI to pedagogical assessments can foster institutional commitment and enhance the process by which universities assess student performance. Sandman (2014) studied the learning styles of 1,100 business students and found that preferred learning styles may depend more on the course than the major, indicating that students have adaptive learning styles.…”
Section: A Brief Review Of Business Educationmentioning
confidence: 99%
“…In the study of Novin, Arjomand & Jourdan (2003), business students were predominantly Assimilators or Convergers who have higher assessment performance that Diverger and Accommodators which is the same with the study of Cekiso, Arends & Mkabile (2015) in South Africa where accounting students were mostly Convergers and in Mei Tan & Laswad (2015) assessment of the business students in introductory accounting that students with 'assimilating' learning style perform better in their assessments than 'diverging' or 'accommodating'. Meanwhile, the Thai business students have adaptive learning styles (Sandman, 2014).…”
Section: Learning Approachmentioning
confidence: 99%